Assessment of Quality of Life Among Patients With Knee Osteoarthritis (Journal of Dhaka Medical College, 2024)
Introduction: Osteoarthritis (OA) is a degenerative joint disease estimated to be the fourth leading cause of disability. Methodology: We conducted a cross-sectional observational study at BSMMU, Dhaka, from April 2018 to March 2019. Our goal was to evaluate the quality of life in knee OA patients in Bangladesh using Short Form-36 (SF-36) Health Survey and Western Ontario and McMaster Universities Osteoarthritis (WOMAC) Index. We collected data through face-to-face interviews, adhering to specific inclusion and exclusion criteria. Results: Most participants were within the 40-59 year age group, with 65.2% of patients reporting a disease duration of 1-5 years. The mean WOMAC scores differed significantly by age (p=0.001), with older patients having higher scores. Gender and monthly income did not significantly impact WOMAC scores (p>0.05). Educational status showed potential significance (p=0.074), but it did not reach statistical significance. There was a strong statistical association between total WOMAC scores and patient age (p=0.001). However, other socio-demographic factors showed no significant differences (p>0.05). Patients with shorter OA knee durations (less than one year) had notably lower WOMAC scores than those with longer durations (1-5 years), with a significant difference (F=16.513, p